Gender Stereotypes in the Short Story Saya di Mata Sebagian Orang by Djenar Maesa Ayu (A Feminist Study) - Wijaya, Guntur Sekti; Lestari, Erawati Dwi (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study aims to analyze gender stereotypes in the short story entitled Saya di Mata Sebagian Orang by Djenar Maesa Ayu using a feminist study approach. This study involves a critical reading of narratives and characters in short stories to uncover the emergence of gender stereotype constructs. This research method uses text analysis and literary interpretation from a feminist perspective. Through this approach, the researcher identifies how the characters in the short story represent gender stereotypes generally related to the traditional roles and characteristics of men and women. The results of the study show that there is a strong gender stereotype in this short story. Women are depicted as trapped in limited roles, such as sexual objects or figures who depend on men. Meanwhile, men are described as authoritarian figures and have dominant power. Feminism studies provide critical insights into the gender stereotypes in this short story and reveal how gender constructions can influence women's experiences and identities in society. This research contributes to understanding gender representation in literature and the importance of fighting stereotypes that limit individual roles and potential.